Examining All-cause and Cause-specific Mortality among Former Prisoners in Pennsylvania. (29th July 2018) - Testa, Alexander; Porter, Lauren C.; Nakamura, Kiminori
Abstract : Former prisoners have a higher than expected risk of death following release from incarceration. However, little is known about the specific risk factors for post-release mortality among former prisoners. The current study uses a unique set of measures obtained from administrative records from Pennsylvania to examine demographic, custodial, behavioral, and criminal history factors that impact mortality risk following release from incarceration. Moreover, this study is the first to assess whether risk factors for post-release mortality are consistent or variable across race and ethnicity. Using data from the Pennsylvania Department of Corrections and mortality records from the Pennsylvania Department of Health we find several demographic, custodial, behavioral, and criminal history measures are related to post-release mortality risk. Moreover, while most risk factors for mortality are generally consistent across race and ethnicity, we find evidence that some custodial and criminal history factors vary by race and ethnicity.